Pengaruh Motivasi Kerja, Kompensasi, Dan Lingkungan Kerja Terhadap Produktivitas Karyawan di PT. Winaros Kawula Bahari Beji-Pasuruan - Bruce Berlian; Veni Rafida (Universitas Negeri Surabaya, 2022)
Company PT. Winaros Kawula Bahari is a Vaname quality frozen shrimp export company. The registered office is Jl Raya Cangkring Malang Km 39.4, Pasuruan, East Java. The aim of this study was to determine the influence of work motivation, remuneration and work environment on employee productivity. In this quantitative study, the population was selected from 50 employees of the raw shrimp department. The sampling technique used is non-probability sampling which is a type of saturated sampling. Multiple regression analysis using SPSS version 25 was used as a research analysis method. Based on the results of the analysis of work motivation, compensation, and work environment variables partially have no effect on the productivity of PT. Winaros Kawula Bahari. The multiple linear regression model in this study is stated simultaneously have a significant effect between the independent variables of work motivation, compensation, and work environment on employee productivity at PT. Winaros Kawula Bahari.